Risk factors of prolonged mechanical ventilation after acute type A aortic dissection surgery: a single-center retrospective study - Chen, Guanying; Li, Zhenyu; Lin, Zhonglin; Su, Quanlin; Ling, Yun; Li, Tianbao; Zhou, Chenbin (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo identify the risk factors of prolonged mechanical ventilation after acute type A aortic dissection (ATAAD) surgery.Methods466 patients undergoing ATAAD surgery from 2016.01 to 2021.01were studied retrospectively. Risk factors of delayed extubation (>48 h of ventilation) were identified using univariate and multivariate logistic regression. LASSO regression was used for variable selection. The ICU stay, hospital stay, complications, and 30-day mortality were analyzed.ResultsAmong the patients, 72% experienced delayed extubation. Risk factors included age (OR 1.042, 95% CI 1.005–1.083, P = 0.031), postoperative serum creatinine (Scr, OR 1.006, 95% CI 1.003–1.010, P < 0.001), and acute lung injury (ALI, OR 5.725, 95% CI 2.777–12.148, P < 0.001). Delayed extubation was associated with increased ICU stays, hospital stays, and complications, including MODS and higher mortality.ConclusionsAge, postoperative serum creatinine, and acute lung injury are significant risk factors for prolonged ventilation. Early identification and management of these factors may improve postoperative outcomes.